Neurotoxicity of Environmental Metal Toxicants - Ortega, Richard; Carmona, Asuncion (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Environmental exposure to metallic neurotoxicants is a matter of growing concern since it may have very significant consequences for human health, from impairing neurodevelopment in children to the neurodegeneration processes involved in aging. The scientific community will face many challenges in identifying and preventing the adverse effects of environmental metal exposure on brain health. This collection of articles provides an overview of current work in the field of neurotoxicology of metal contaminants, from the identification of emerging toxic compounds, to the assessment of environmental exposures and associated risks, through the description of the molecular mechanisms involved in neurotoxicity.